Fabrication and intrinsic physical property of spin-gapless like Heusler alloy CoFeMnSi single crystal. (January 2021) - You, Caiyin; Fu, Huarui; Li, Yunlong; Ou, Zhiqiang; Ma, Li; Tian, Na; Wang, Vei
Graphical abstract: Highlights: The fabricated CoFeMnSi compound presents the high quality of single crystal. Magnetic properties confirm the potential of spin gapless behavior. A dependence of resistivity on crystallographic orientation was clarified. Abstract: The Heusler-type spin gapless semiconductors (SGSs) have been extensively studied owing to their characteristic band structure, i.e., zero band gap of majority electrons and clear band gap of minority electrons. To date, the intrinsic physical property of the correlated single crystal is somewhat unclear, leading to difficulty in understanding the principle physical mechanism. In this study, we successfully fabricated the single crystal of the potential spin-gapless semiconductor Heusler CoFeMnSi compound and investigated its intrinsic physical properties. The saturation magnetization of the single crystal at 50 K is ∼99.55 emu/g (∼3.53 μB /f.u.), and the single crystal exhibits a Curie temperature of 826 K. The resistivity of single crystal shows anisotropy: the temperature dependence of resistivity along the [111] direction is completely different from the behavior along [001] and [100] directions. Furthermore, when the temperature was >135 K, a semiconductor-like behavior was observed along the [111] orientation.